1995
DOI: 10.3109/00016349509009940
|View full text |Cite
|
Sign up to set email alerts
|

Infection markers during labor at term

Abstract: Serum levels of C-reactive protein (CRP), white blood cell count (WBC), amniotic fluid white blood cells (Gram staining) and leukocyte esterase (LE) activity were measured serially and prospectively in 30 pregnant women in labor at term. Results were retrospectively compared with amniotic fluid bacterial culture results. Leukocyte esterase activity was measured by the dipstick test (Nephurtest) and an in vitro photometric method. Amniotic fluid samples were collected through an intrauterine transvaginal pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…However, many studies have doubted the value of CRP in diagnosing intrauterine infection. [39][40][41] Reason for doubt could be the low specificity of CRP, the fluctuating values at different gestational ages, and the correlation with duration of labor. [39][40][41] In preterm neonates, maternal serum IL-6 concentration has shown to be a sensitive and specific marker for chorioamnionitis.…”
Section: Maternal Serummentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies have doubted the value of CRP in diagnosing intrauterine infection. [39][40][41] Reason for doubt could be the low specificity of CRP, the fluctuating values at different gestational ages, and the correlation with duration of labor. [39][40][41] In preterm neonates, maternal serum IL-6 concentration has shown to be a sensitive and specific marker for chorioamnionitis.…”
Section: Maternal Serummentioning
confidence: 99%
“…[39][40][41] Reason for doubt could be the low specificity of CRP, the fluctuating values at different gestational ages, and the correlation with duration of labor. [39][40][41] In preterm neonates, maternal serum IL-6 concentration has shown to be a sensitive and specific marker for chorioamnionitis. 42 In line with this, Smulian et al have shown that histologic chorioamnionitis is associated with higher maternal IL-6 levels in term pregnancies 43 ( Table 2 [A]).…”
Section: Maternal Serummentioning
confidence: 99%
“…After rupture of the membranes, up to 70% to 90% of amniotic fluid becomes colonized with microbes, even during normal delivery. [1][2][3][4] Intrauterine bacterial infection or inflammation in the gestational tissues is commonly thought to be the cause of the onset of preterm labor, even when the membranes are intact. 5 Several studies have focused on the effect of maternal infections and antibiotic administrations during pregnancy and at delivery on the development of asthma among offspring.…”
mentioning
confidence: 99%
“…Leukocyte esterase, present in granulocytic leukocytes, catalyzes and reacts with the reagent to produce a purple color that is detected by the reader. This procedure has been used in clinical research as a screening method for urinary tract infection (Keski-Nisula et al, 1995).…”
Section: Methodsmentioning
confidence: 99%